SISTEM AKUNTANSI PEMBELIAN BARANG DAGANGAN PADA KOPERASI PEGAWAI NEGERI-KOPERASI DEPARTEMENT AGAMA PANGKAT (KPN-KOPDAP) - zulkifli, zulkifli; Nuhung, Mahmud (Universitas Muhammadiyah Makassar, 2018)
The results of the research obtained include exposure to the elements contained in the accounting system for purchasing merchandise, related functions, documents used, accounting records used, and the methods used in the accounting system for purchasing merchandise at the Cooperative. Civil Servants - Cooperatives Department of Religion Pangkep (KPN-KOPDAP). From the results of the study, conclusions can be drawn on the Civil Servant Cooperative - Pangkep Department of Religion Cooperative (KPN-KOPDAP), there are several elements contained therein: 1) Purchase Request, 2) Price Bid Request, 3) Purchase Order, 4) Goods Receipt , 5) Debt Registrar. Civil Servants Cooperative - Pangkep Religion Department Cooperative (KPN-KOPDAP) also has two types of credit purchase systems, namely: 1) Shop Order, 2) Salesman Canvas.